ENSURING THE EFFECTIVE APPLICATION OF EDUCATIONAL MODELS AND INTERACTIVE TEACHING TECHNOLOGIES IN THE EDUCATION SYSTEM - I.S. Soliyev; M.Sh. Nuriddinova (Modern American Journals, 2025)
This article analyzes various educational models and the effective use of interactive teaching technologies in the education system. It emphasizes the importance of implementing new pedagogical methods and technologies to enhance students’ knowledge and skills and improve the performance of educators. The article highlights the potential of interactive teaching technologies—such as reading and writing strategies, group work, multimedia tools, and online platforms—in promoting active student engagement and collaboration. Special attention is given to the development of students’ creative thinking and problem-solving abilities through the integration of modern technologies in the learning process.
Keywords: Educational models, interactive teaching technologies, education system, innovative pedagogy, multimedia learning, teacher professional development, student engagement methods.